2020
DOI: 10.1002/pchj.359
|View full text |Cite
|
Sign up to set email alerts
|

Children's effortful control moderates the relationship between parental psychological control and adolescents’ depressive symptoms

Abstract: The present study examined the interactions of adolescents' temperamental effortful control and parental psychological control on adolescents' depressive symptoms in China. A total of 440 adolescents between the ages of 14 and 20 years (M age = 15.7) participated in this study. Data on parental psychological control, adolescents' depressive symptoms and effortful control were collected from selfreports. Results showed that adolescents' effortful control moderated the link between paternal psychological control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Therefore, maternal psychological control may be more likely to in uence and be in uenced by children's problem behaviors. Empirical studies seem to be in alignment, Li et al [31] found that maternal rather than paternal psychological control positively predicted depressive symptoms in adolescents. Gao et al [32] found that early adolescent social anxiety could predict mother-reported psychological control rather than father-reported psychological control, showing the in uence of child-driven effects on mothers.…”
Section: Bidirectional Relationships Between Psychological Control An...mentioning
confidence: 96%
“…Therefore, maternal psychological control may be more likely to in uence and be in uenced by children's problem behaviors. Empirical studies seem to be in alignment, Li et al [31] found that maternal rather than paternal psychological control positively predicted depressive symptoms in adolescents. Gao et al [32] found that early adolescent social anxiety could predict mother-reported psychological control rather than father-reported psychological control, showing the in uence of child-driven effects on mothers.…”
Section: Bidirectional Relationships Between Psychological Control An...mentioning
confidence: 96%
“…Parental psychological control may cause unhealth mental problems, especially depressive symptoms. Both mother and father's psychological control are associated with children's internalization, typically depressive symptoms [5], but mother's is stronger than father's [3,6]. Research shows that father and mother use more psychological control on boy rather than girl [5].…”
Section: Parental Psychological Control's Gender Differencesmentioning
confidence: 97%
“…It should be known that children's own temperaments cannot be ignored. Temperaments are risk factors for children to face parental psychological control [6]. Parents use different rearing methods to children whose temperaments are different.…”
Section: Children's Temperamentsmentioning
confidence: 99%
“…Dozens of articles -75 articles among 755 articles we identified on PPChave cited the relativistic argument that PPC could be less damaging in interdependent cultures than independent cultures (Abd-El-Fattah & Abdulrahman Fakhroo, 2012; Ahmad et al, 2013;Akcinar & Baydar, 2014;Basili et al, 2021;Bullock et al, 2018;Chao & Aque, 2009;Cheah et al, 2019;Chen et al, 2016;Chen et al, 2021;Chen-Bouck et al, 2019;Chen-Bouck & Patterson, 2020;Ching et al, 2021;Chou & Chou, 2018;Chyung et al, 2021;Davidov et al, 2021;Doan et al, 2017;Fang et al, 2021;Fung et al, 2017;Gao et al, 2021Gao et al, , 2022Gargurevich & Soenens, 2016;Grolnick, 2012;He et al, 2019;Henry et al, 2018;Hsieh, 2020;Kakihara & Tilton-Weaver, 2009;Kho et al, 2019;Kim et al, 2017;Kins et al, 2012;Lau & Fung, 2013;Lau et al, 2022;Li et al, 2016;Li et al, 2018;Li et al, 2020;Liga et al, 2017;Lin et al, 2022a;Liu et al, 2019;Loeb et al, 2021a;Louie et al, 2013;…”
Section: Operationalization Of Ppc In Cross-cultural Studiesmentioning
confidence: 99%